Geochemistry, UPb geochronology, and Sr-Nd-Hf isotope systematics of a SW-NE transect in the southern Peninsular Ranges batholith, Mexico: Cretaceous magmatism developed on a juvenile island-arc crust - Contreras-López, Manuel; Delgado-Argote, Luis Alberto; Weber, Bodo; Torres-Carrillo, Xóchitl Guadalupe; Frei, Dirk; Gómez-Alvarez, Doris Karina; Tazzo-Rangel, María Daniela; Schmitt, Axel Karl (Lithos, 2021)
The Peninsular Ranges batholith (PRB) is a North American Cordillera segment with a protracted record of subduction-related magmatism (177-92 Ma). However, such a record is regionally fragmented, showing broad petrologic variations challenging to integrate into a coherent geologic evolution history. Here, we present a petrogenetic study of Cretaceous plutons in the southern PRB along the Sierra El Arco-San Francisquito transect (SW-NE) perpendicular to the paleotrench. The Middle Jurassic-Early Cretaceous (166-140 Ma) magmatism developed as an island arc with sedimentary rocks of intra-arc and oceanic marginal basins. At the Sierra El Arco, the Calmallí pluton intruded the Jurassic arc sequence. The basic to intermediate rocks of the Calmallí pluton show εSrt (average -3.6), εNdt (average +3.3), and εHft values (average +6.0) that suggest an origin from mantle-derived melts with minor contamination. These rocks display almost flat rare earth elements (REE) patterns and Eu anomalies suggesting plagioclase fractionation. East of the Calmallí pluton from the Piedra Blanca to the San Francisquito region, granodiorite and granite (100-92 Ma) are continuously exposed. The εSrt (average +3.1), εNdt (average +1.1), and εHft (average +2.6) isotopic signatures in the acid rocks suggest a mantle-derived melt genesis with increased contamination. Most granodioritic and granitic rocks display a characteristic depleted-HREE pattern without Eu anomalies, suggesting differentiation under the influence of garnet. The Jurassic-Cretaceous (166-92 Ma) magmatism displays an εSrt vs. εNdt correlation trend, indicating progressive contamination of mantle-derived magmas with a recycled crust. SrNd and NdHf isotopic mixing curves suggest the assimilation of the metasedimentary Triassic basement of NW Mexico instead of the considerably older and isotopically evolved Precambrian basement. The integration of this work with data from NW Mexico suggests a continuous magmatic activity from the Middle Jurassic to the Late Cretaceous. We consider the geochemical, isotopic, and temporal variation of the PRB indicative of natural heterogeneities along the trench axis of a long-lived arc system (crustal thickness and paleogeography) due to continuous subduction of the Farallon plate below the North American plate.